Cultural Transformation and the Work Environment of Civil Servants Based on the Values of the Qur’an - Ruddy Yunivan; Nur Arfiyah Febriani; Made Saihu; Abdul Aziz; Afif Faizin (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This research is motivated by the critical role of work culture and climate in enhancing the performance of State Civil Apparatus (ASN) within the educational sector. The primary objective of the study is to analyze and describe the work culture and climate at Senior High School (SMA) 2 Krakatau Steel Cilegon, Banten, through an Al-Qur'an perspective. This study employs a qualitative methodology, utilizing a thematic (maudhu'i) interpretation approach for Qur'anic analysis combined with exploratory field research. Data were gathered through observation, in-depth interviews, and documentation. The results indicate that a productive work culture and a harmonious climate are achieved by implementing four holistic elements derived from Qur'anic signals: integrity (al-amanah), professionalism (al-itqan), responsibility (al-mas’uliyah), and exemplary leadership (al-qudwah). The findings suggest that the integration of Islamic values—such as honesty, loyalty, and mutual respect—significantly increases employee motivation and organizational performance. The study concludes that synergizing religious values with professional duties creates a sustainable and inclusive educational environment, positioning SMA 2 Krakatau Steel Cilegon as an inspirational model for other institutions in Banten.